Communication process between OFW parents and their left-behind adolescent children - Sulla, Crestian Joseph Badion; Dare, Evangeline M. (2011.)
This study aimed to describe the process of communication between Overseas Filipino Worker (OFW) parents and their left-behind adolescent children. It also determined the adolescents' perception and level of satisfaction on family communication and family relationship. Quantitative and qualitative design was used in this study. Sixty three adolescent respondents from the National College of Business and Arts and the University of the Philippines participated in the study. They were chosen using the combination of snowball and convenience sampling. A survey questionnaire was used to gather data on the adolescents' profile, the communication process such as the mode, medium, frequency, duration, topics and flow of communication. Likert-typed scales were also used in this study to measure the level of satisfaction of adolescent on the family communication and family relationship. A focused group discussion of 10 adolescent respondents was also used in the study. With emergence of new and high technology, communicating despite distance has become cheaper, easier and more conducive to direct interaction. Texting or short message was the number one option for OFW families to communicate with each other. The frequency of contact increased but the length or duration of the interaction is shortened. These families combined and used multiple modes of communication. The usual topics of conversations focused on matters related to finances/money, family life and education. This study showed that family income affects the communication process. It also revealed that it was the left-behind adolescents who initiate conversation with their OFW parents. In contrast, it was the left-behind parent who was usually sought out by the parent abroad. Adolescent respondents reported that communication with their OFW parents became deeper and more open due to the desire to overcome physical separation and the initiative to keep each other updated. results showed that adolescents are satisfied with the whole communication process, and they felt generally happy and excited when talking with their OFW parents. This study also finds out that adolescents perceived their family communication and family relationship to be highly satisfactory while the level of satisfaction in both family communication and relationship ranged from high to very high; they feel good about their communication and relationship and have few concerns. Lastly, results pointed out that there is no correlation between these two variables.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Interpersonal communication in adolescence -- Philippines; Communication in families -- Philippines